Effect of jig constraint state during welding process on fatigue properties of Al/CFRP dissimilar welds and fatigue life evaluation based on singular stress. Issue 10 (12th May 2020) - Ogawa, Yuki; Nakahara, Fumiya; Akebono, Hiroyuki; Tanaka, Kojiro; Sugeta, Atsushi
Abstract: Manufacturers have been promoting multimaterial designs. So the dissimilar material welding methods are being developed. Especially, heat welding technology, which is a direct joining by local heating, has been focussed. Therefore, this study used a heat welding technology for friction stir spot welding of aluminium alloy and carbon fibre‐reinforced plastic. This study investigated the effect of changes to jig constraint of joined members on the fatigue properties of joints. Also, the fatigue life estimation was carried out by considering the singular stress at the welding joint interface. As a result, the fatigue strength of joint in a less constrained state is higher than that in a more constrained state. The singular stress intensity at the slit tip was uniformly predicted by the differences in welding parameters of joints.